Crop yield and water saving potential for AquaCrop model under full and deficit irrigation managements - Abdalhi, Mohmed A.M.; Jia, Zhonghua (Italian Journal of Agronomy, 2018)
The study review selected researches related to full and deficit irrigation managements simulated with AquaCrop model for various field crops (group 1) and vegetables/spices (group 2). In order to evaluate the application of full and deficit irrigation vs crop yield and water use, publications from 1979 to 2018 were reviewed. With a view to find the significance variations in modelled crop yield, irrigation water use and yield reductions corresponding to water saving potential (WSP). Additionally, reporting brief summary of findings, recommendations linked to model simulation and proposed some gaps for further investigations. The findings confirm that there are significant differences in yield reductions corresponding to water saving with inference R2 was 0.372 in crop group 1 and 0.117 in group 2 during study. Simulated yield in evaluated field crops and vegetables/spices varied between 14.44 to 0.012 t/ha in full ETc and 10.72 to 0.004 t/ha in deficit ETc. The water saving potential, in the two groups of field and vegetable/spice crops revealed that, with acceptance of yield reduction equivalent 2.66 and 29.03% save irrigation water equal to 23.68 and 80% while the reduction of 41.79 and 26.86% of yield saved 28.87 and 82.1%. The maximum water save values are higher than that reported for deficit irrigation in previous publications. Some suggested points related to this research need further studies e.g. evaluating the big differences in crop yields and irrigation water applied resulted with AquaCrop under full and deficit irrigation management and justification of high WSP corresponding less crop yield reduction.